Cash flow vs. collateral‐based credit. Issue 2 (15th March 2013) - Cassano, Francesca; Jõeveer, Karin; Svejnar, Jan
Abstract We study factors affecting micro, small and medium‐sized enterprises (MSMEs) receiving loans and the effect of these loans on MSMEs performance. We study two types of loans – a new type based on cash flows and a traditional‐style loan based on collateral. We use unique surveys of MSMEs from Bulgaria, Georgia, Russia and Ukraine. We find that MSMEs receiving a cash flow or collateral loan in the past are more likely to receive the same type of loan (and larger sized) in the future and that cash flow loans may be the preferred form of credit. Both types of loans are related positively to most performance indicators, enabling the MSMEs for instance to be more profitable and expand production. The cash flow loans also appear to be particularly attractive credit delivery schemes for micro and small enterprises. Finally, the effects of the smallest loans are often negative, suggesting that the minimum loan size is an important policy issue.